Rancang Bangun Wireless Access Point dengan Capsman dan Mac Mask Access list - Zaenal Mutaqin Subekti; Subandri Subandri (Politeknik Harapan Bersama, 2019)
In the era of millennial needs using the internet became the primary needs of everyone, to connect to the internet one of them by connecting through an access point. The problem that occurs is the difficulty of getting legal internet access that is already connected to an access point then moving place or room. Because the number of access point devices installed with SSID (Service Set Identifier) is different for each device that the user needs to log in again to get internet access, and there is no filtering of users who are entitled to use hotspot facilities based on certain devices. With the number of access points being hotspots, this becomes a consideration for network managers to set hotspot passwords or other settings, this is a new challenge for network managers. Therefore, to overcome this problem a wireless access point management system was built that uses centrally using CAPsMAN (Controller Access Point System Manager) and MAC Mask Access Lists as filtering. By using the NDLC (Network Development Life Cycle) method in floating network design.